2011
DOI: 10.1177/0003319710395561
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Ankle Vascular Index Could Reflect Plaque Burden in the Coronary Artery

Abstract: Cardio-ankle vascular index (CAVI) using the volume plethysmographic method is a noninvasive atherosclerotic indicator which is not influenced by blood pressure. Coronary intravascular ultrasound (IVUS) is a reliable technique to measure progression of atherosclerosis. The association between CAVI and IVUS has not been reported. The aim of this study was to evaluate the association between CAVI and the plaque burden measured by IVUS in the left main coronary artery (LMCA) in patients with coronary heart diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 28 publications
0
39
0
3
Order By: Relevance
“…CAVI reflects the stiffness of all arterial segments, and the femoral and tibial artery as a whole. In recent studies, it has been reported to be associated with the severity of atherosclerosis [13,22]. In this study, we determined a relationship between CAVI and the complexity of CAD assessed by SS in nondiabetic patients.…”
Section: Discussionmentioning
confidence: 98%
“…CAVI reflects the stiffness of all arterial segments, and the femoral and tibial artery as a whole. In recent studies, it has been reported to be associated with the severity of atherosclerosis [13,22]. In this study, we determined a relationship between CAVI and the complexity of CAD assessed by SS in nondiabetic patients.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, early results show easy measurement 18) with good reproducibility 31) and risk predictability 4) . The CAVI has been reported to be related to hypertension 6) , diabetes mellitus 7) , hyperlipidemia 8) , smoking 9) and epicardial adipose tissue 10) and consistently shows a good correlation with components of atherosclerotic disease, such as coronary artery disease 7,11,32) , the cardiac function 12,13) , cerebrovascular disease 14,15,33) , the cognitive function 16) and kidney disease 17) . Recent studies have reported that the CAVI is decreased by controlling hypertension 6) and diabetes mellitus 34) and abstaining from smoking 35) .…”
Section: Arterial Agingmentioning
confidence: 99%
“…CAVI is an index of atherosclerosis, which is independent of blood pressure and has been validated in various populations [23][24][25] . CAVI has consistently shown a good correlation with known cardiovascular risk factors and atherosclerotic disease, such as coronary artery disease, carotid arteriosclerosis and cerebrovascular disease.…”
Section: Cavi and Atherosclerosismentioning
confidence: 99%